Alleviation of drought stress through foliar application of thiamine in two varieties of pea (Pisum sativum L.) - Kausar, Abida; Zahra, Noreen; Zahra, Hina; Hafeez, Muhammad Bilal; Zafer, Sara; Shahzadi, Abida; Raza, Ali; Djalovic, Ivica; Prasad, PV Vara (Plant signaling & behavior, 2023)
Drought stress poorly impacts many morphological and physio-biochemical processes in plants. Pea (Pisum sativum L.) plants are highly nutritious crops destined for human consumption; however, their productivity is threatened under drought stress. Thiamine (vitamin B1) is well-known essential micronutrient, acting as a cofactor in key metabolic processes. Therefore, this study was designed to examine the protective effect of foliar application of thiamine (0, 250, and 500 ppm) on two varieties of pea plants under drought stress. Here, we conducted the pot experiment at the Government College Women University, Faisalabad, to investigate the physio-biochemical and morphological traits of two pea varieties (sarsabz and metior) grown under drought stress and thiamine treatment. Drought stress was applied to plants after germination period of 1 month. Results showed that root fresh and dry weight, shoot fresh and dry weight, number of pods, leaf area, total soluble sugars, total phenolics, total protein contents, catalase, peroxidase, and mineral ions were reduced against drought stress. However, the application of thiamine (both 250 and 500 ppm) overcome the stress and also enhances these parameters, and significantly increases the antioxidant activities (catalase and peroxidase). Moreover, the performance of sarsabz was better under control and drought stress conditions than metior variety. In conclusion, the exogenous application of thiamine enabled the plants to withstand drought stress conditions by regulating several physiological and biochemical mechanisms. In agriculture, it is a great latent to alleviate the antagonistic impact of drought stress on crops through the foliar application of thiamine.